From Krausism to positivism: Development of Spanish historical and philosophical thought in the late 19th–early 20th centuries as viewed by Spanish scholars - N.V. Antonova; N.V. Arzhantseva (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article considers the development of Spanish historical thought between the mid-19th and the early 20th centuries. The main stages in the development of the Spanish historical tradition are singled out. The features and driving forces of each stage are analyzed. The representatives of the traditions under study are given in chronological order. Their contributions to Spanish historical thought are specified. The brightest ideas of the most prominent scholars that reveal the unique nature of Spanish historical thought are discussed. Moreover, it was these ideas that provoked the dramatic changes in the Spanish interpretation of history in general, as well as in the approaches and methods of its study. The gradual movement of Spanish historiography to its current state is presented through a variety of views from the works of Spanish historians. The common interpretations of every phenomenon or trend are supplemented with alternative theories and concepts. The progress of Spanish historical thought is traced up to the early 20th century. The first step is marked by the adaptation of the ideas of Krausism, which largely affected the subsequent evolution of Spanish historical thought. The period that followed is associated with positivist ideas; its characteristics and various interpretations by Spanish scholars are summarized. The results obtained make it possible to conclude about the basic features typical of the development of Spanish historical thought in the late 19th–early 20th centuries.